2014
DOI: 10.1002/elsc.201300129
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Aspergillus nigerATCC 1015 on bionatural structures for lipase production

Abstract: Lipase of Aspergillus niger ATCC 1015 was immobilized onto matrices of a structural fibrous network (SFN) of pawpaw (Carica papaya) wood and vegetable sponge (VS) of (Luffa aegyptiaca) by physical entrapment through solid‐state fermentation. SFN‐ and VS‐immobilized lipases were characterized in terms of their operational and storage stability. The immobilizates were cross‐linked with ethanolic formaldehyde (EF), formaldehyde (F) and glutaraldehyde (GA). Ninety percent enzymatic activity was retained with GA as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The optimum temperature of the free lipase was about 45°C, whereas that of the immobilized enzyme was increased to 55°C ( Figure 3 ). Osho et al [ 12 ] reported in their study on the effect of reaction temperature on lipase activity using structural fibrous network of papaya and vegetable sponge-immobilized lipases of A. niger ATCC 1015 recorded optimum temperature of 45°C for both matrices and ascribed the reason to a consequence of enhanced thermal stability. In support of this finding, Allenza et al [ 26 ] and Kitano et al [ 27 ] reported that the activation energy of the immobilized enzyme was lower than that of the free enzyme (i.e., the higher the temperature, the lower the activation energy), because the internal diffusion of the substrate into the carrier-enzyme system was the rate-limiting the process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimum temperature of the free lipase was about 45°C, whereas that of the immobilized enzyme was increased to 55°C ( Figure 3 ). Osho et al [ 12 ] reported in their study on the effect of reaction temperature on lipase activity using structural fibrous network of papaya and vegetable sponge-immobilized lipases of A. niger ATCC 1015 recorded optimum temperature of 45°C for both matrices and ascribed the reason to a consequence of enhanced thermal stability. In support of this finding, Allenza et al [ 26 ] and Kitano et al [ 27 ] reported that the activation energy of the immobilized enzyme was lower than that of the free enzyme (i.e., the higher the temperature, the lower the activation energy), because the internal diffusion of the substrate into the carrier-enzyme system was the rate-limiting the process.…”
Section: Resultsmentioning
confidence: 99%
“…This includes agarose beads, alginate beads [ 3 ], chitosan beads [ 9 ], k-carrageenan beads [ 10 ], and nanogel beads [ 11 ]. Osho et al [ 12 ] have reported the use of bionatural matrices—structural fibrous network (SFN) and vegetable sponge (VS)—for their ability to entrap or immobilize lipase and the effects of immobilization on the temperature, pH, operational stability, and reusability of the lipase were investigated. In the present study, Aspergillus niger F7-02 lipase was immobilized by entrapment in polysaccharide hydrogel beads of Irvingia gabonensis matrix at optimized immobilization conditions for biotechnological industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the immobilization of lipase successfully enhanced its pH stability, especially in slightly acidic environments. A relative activity above 75 % was achieved for the immobilized lipase stored at 4 C and 50 % at 28 C until the fourth week of storage for both supports [81].…”
Section: Obtainment and Properties Of Lipases From Aspergillusmentioning
confidence: 95%
“…The positive influence of the immobilization process was observed on the thermal stability of the enzyme, since a longer half-life t 1/2 and lower deactivation constant were obtained with the encapsulated lipase when compared with the free lipase [80]. Osho et al [81] tested the lipase immobilization produced by A. niger ATCC 1015 in matrices of a structural fibrous network of pawpaw (Carica papaya) wood and vegetable sponge (Luffa aegyptiaca) by entrapment. The authors showed that the immobilization of lipase successfully enhanced its pH stability, especially in slightly acidic environments.…”
Section: Obtainment and Properties Of Lipases From Aspergillusmentioning
confidence: 99%
“…Additionally, papaya trunk wood is very cheap and abundantly available. Several microorganisms have been immobilized in papaya trunk wood, i.e., Aspergillus niger (Osho et al, 2014), Aspergillus tamarii (Maduka et al,Halim et al / JIPK,13(2):208-221…”
mentioning
confidence: 99%